Perception of the Use of the Direct Observation of Procedural Skills in Occupational Therapy Postgraduate Year Training in Taiwan: Survey of the Perspectives of Trainees and Supervisors - Yi-chia Liu; Yi-chen Lee; Pai-chuan Huang; I-Hui Lee; Keh-chung Lin (Hindawi-Wiley, 2023)
Introduction. Assessment of clinical competence is a significant part of the training for young occupational therapists (OTs). Objective and systematic assessment allows both supervisors and trainees to be aware of the training objectives and monitor the progress. The direct observation of procedural skills (DOPS) is a work-based assessment to evaluate professional knowledge, skills, and attitude in clinical training. This study investigated the perspectives of OT educators and trainees on using DOPS and their discrepancy for OT postgraduate year (PGY) training. Methods. This study used a quantitative online survey. Eighty-six supervisors and 41 trainees of OT PGY training programs from 95 hospitals returned the questionnaire (a 90.5% return rate), and 64 supervisors and 30 trainees who used DOPS were analyzed. Outcomes included the practicality in using the DOPS in clinical settings, the ease of rating the DOPS, and advantages and the disadvantages of the DOPS. Results. Most respondents reported that completing one DOPS required at least 11 minutes for direct observation (11-40 minutes: teacher 92.2%; trainee 80.6%). Most respondents (teacher 96.9%, trainee 96.8%) had feedback after direct observation of DOPS, and about half of the feedback assessments took 5 to 10 minutes (teacher 53.1%, trainee 48.4%). Most OT educators and trainees agreed that clinical resources were sufficient and that DOPS matched with OT training goals, benefited OT competence training, and had a fair, objective, and consistent scoring system. Significantly higher percentages of OT trainees felt stressed in and satisfied with the DOPS assessment than trainers. Differences between teachers and trainees regarding easiness of rating DOPS items were not significant. Conclusion. Most OT educators and trainees agreed that DOPS was a practical and appropriate assessment for OT PGY training.